ANATOMI KORUPSI DAN PERAN PENDIDIKAN: UPAYA MENGURAI BENANG KUSUT KORUPSI MELALUI PENDIDIKAN - Mujib Ridlwan (LPPM Institut Agama Islam Al-Hikmah Tuban, 2014)
Abstract: There are two topics in this paper, what is the anatomy of corruption,in which it raises a question of how corruption can be mushrooming in Indonesiaand how to heal the ulcers of corruption. And what is the role of education incombating corruption? There are three (3) important aspects in understanding theanatomy or basic framework of corruption, (a) the monopoly of power; (b) theunlimited authority or discretion, and (c) no clear accountability orresponsibility. The trigger of the corrupt behavior is due to such factorseconomy, opportunities and low morality. The role of education in the field ofcombating corruption is to improve moral quality. Education here does not meansuch a school educational institution. It is also related to the education gainedfrom households and the environment (home or working places).